2017
DOI: 10.1002/bmb.21086
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a web‐based introductory bioinformatics course for non‐bioinformaticians that incorporates practical exercises

Abstract: A recent scientific discipline, bioinformatics, defined as using informatics for the study of biological problems, is now a requirement for the study of biological sciences. Bioinformatics has become such a powerful and popular discipline that several academic institutions have created programs in this field, allowing students to become specialized. However, biology students who are not involved in a bioinformatics program also need a solid toolbox of bioinformatics software and skills. Therefore, we have deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Conferences and workshops also serve as essential sources of bioinformatics skills for some respondents (28.6%), while a small percentage (15.5%) used online resources to learn bioinformatics skills. These later may have benefitted from the opportunity provided by the H3ABioNet (Gurwitz et al, 2017) in addition to other training opportunities such as those used in other countries (Cattley and Arthur, 2007;Ding et al, 2014;Vincent et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conferences and workshops also serve as essential sources of bioinformatics skills for some respondents (28.6%), while a small percentage (15.5%) used online resources to learn bioinformatics skills. These later may have benefitted from the opportunity provided by the H3ABioNet (Gurwitz et al, 2017) in addition to other training opportunities such as those used in other countries (Cattley and Arthur, 2007;Ding et al, 2014;Vincent et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conferences and workshops also serve as essential sources of bioinformatics skills for some respondents (28.6%), while a small percentage (15.5%) used online resources to learn bioinformatics skills. These later may have bene tted from the opportunity provided by the H3ABioNet [19] in addition to other training opportunities such as those used in other countries [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Langheinrich and Bogner [67] reported that computer-supported gene technology module increased the students' conceptual understanding of the structure of DNA. It has been reported that the web-based bioinformatics module not only provides bioinformatics information, but also develops specific knowledge (informatics, biological sequence analysis, and structural bioinformatics) and skills [68]. In this study, virtual laboratory (Polymerase Chain Reaction) and web-based teaching (Bioinformatics: Phylogenetic Prediction) were used in biotechnology teaching within the scope of innovative teaching approaches.…”
Section: Discussionmentioning
confidence: 99%